Prevalence of low bone mass and vitamin D deficiency in pediatric and adult patients with cystic fibrosis in Republic of Macedonia - Jakovska, Tatjana; Mecevska-Jovcevska, Jasmina; Petlickovski, Aleksandar; Fushtik, Stojka; Zorcec, Tatjana (My University, 2014)
Bone disease in cystic fibrosis (CF) has become a topic of widespread interest and impact in the CF community. Recently, some biochemical markers have been proposed to provide information about the dynamics of bone turnover. Only limited information is available for young patients. Imbalance between bone formation and degradation in CF especially in puberty has become an important issue for developing osteopenia. Influence of vitamin D receptor alleles on BMD suggests that these polymorphisms have a greater influence on BMD in childhood. The aim of our study was to assess prevalence of vitamin D deficiency and osteopenia in pediatric and adult CF patients.